PERSPEKTIF KEBIJAKAN BERBASIS BUKTI TERHADAP IMPLEMENTASI KEBIJAKAN OPEN DEFECATION FREE (ODF) DI DESA MERI KABUPATEN PURBALINGGA - Ranjani, Ranjani; Trianfano, Andri Trianfano; Agustina, Alfriansa Agustina; Permana, Doni Agustia; Sari, Inti Novita (Universitas Diponegoro, 2023)
ODF (Open Defecation Free) or Stop Open Defecation is a condition when every individual in the community does not defecate openly. Open defecation (BABS) behavior is still common in Meri Village. Thus, this research will examine in more depth the government's efforts to achieve ODF in Meri Village. This study uses a qualitative approach to the implementation of the first pillar in evidence-based policy theory (Evidence Best Policy) in Meri Village. The research design used is a descriptive research design with a case study approach. The results of the study show that various efforts have been made by the government in realizing the achievement of Open Defecation Free (ODF) in Meri Village, Purbalingga Regency. So that in terms of compliance from the side of the village government as the program implementer it can be said to have complied, but on the community side as the program target has not fully complied. This is because in practice, the implementation of the ODF program in Meri Village still faces various obstacles, such as the large number of people who still defecate openly, and the conversion of the function of the river as an estuary for sewage disposal from residents' latrines because many residents do not yet have a septic tank.